Destination : healthy tourism in the Caribbean. - HOSPEDALES, C. James (1997)
Notes that the future of Caribbean tourism is compromised by recent reports of disease outbreaks. Reports on the public-private partnership programme to improve the quality and competitiveness of hotels by providing a safer and healthier environment to guests and staff while recognizing a fact overlooked in the past : the crucial role of health in creating a more profitable, sustainable, and high quality tourism product.